THE INFLUENCE OF FOLIAR FERTILIZING ON THE APRICOT YIELD AND THE CHEMICAL COMPOSITION OF APRICOT LEAVES - Marina T. Stojanova; Aziz Şatana; Monika Stojanova; Dragutin Djukic (The Balkans Scientific Center of the Russian Academy of Natural Sciences, 2023)
The effect of foliar fertilizing on the yield and the chemical composition of leaves from Roxana apricot cultivar grown in Skopje Region was determined. The experiment was set in four variants and three repetitions. The variants were: Control (untreated); Humustim (organic matter 58.63%, dry matter 12.38%, humic acids 20.40%, fulvo acids 2.15%, N 3%, P2O5 1.02%, K2O 7.92%, Ca 3.70%, Mg 1.03 %); NPK+Ever green with Me (55% organic matter, 2%w/w Mg, 2%w/w Fe, 2%w/w Zn, 2% w/w Mn, 0.5 %w/w Cu, 0.5 %w/w B); NPK+Biolinfa (34% organic matter, 3 %N, 5.80 % K2O);The distance of fruit planting was 5 m row by row and 4 m in the rows. In each variant and repetition 20 plants were included, and total in all experiment 240 plants were involved. Three foliar treatments were applied with given above fertilizers at a concentration of 0.4%. At the end of November, soil fertilizing with the fertilizer Polyfeed NPK 11-44-11 (450 kg∙ha-1) was done. Before setting up the experiment, soil agrochemical analyses were made, and was concluded good fertility with nitrogen, but medium fertility with phosphorus and potassium. The foliar fertilizing has a positive influence on the yield and the chemical composition of apricot leaves. The highest (p<0.05) average apricot fruit yield (33.150 kg∙ha-1) was determined in the leaves from the variant treated with fertilizer NPK+Ever green with Me (55% organic matter, 2%w/w Mg, 2%w/w Fe, 2%w/w Zn, 2% w/w Mn, 0.5 %w/w Cu, 0.5 %w/w B). The lowest (p<0.05) apricot fruits yield (31.2700 kg∙ha-1) was determined in the control variant. The highest (p<0.05) average content of nitrogen (3.12%), phosphorus (0.42%) and potassium (3.92%) was determined in the variant NPK+Ever green со Me (55% organic matter, 2% w/w Mg, 2% w/w Fe, 2% w/w Zn, 2% w/w Mn, 0.5% w/w Cu, 0.5% w/w B). The highest (p<0.05) average content of calcium (2.15%) and magnesium (0.55%) were determined in the leaves from variant NPK+Oligomix (1.20% B, 0.10% Cu, 4% Fe, 1.50% Mn, 0.10% Mo, 2% Zn). The highest (p<0.05) average content of iron (199 mg·kg-1), manganese (121 mg·kg-1), B (67 mg·kg-1), zinc (105 mg·kg-1) and molybdenum Mo (59 mg·kg-1) was determined in the apricot leaves from variant NPK+Ever green with Me (55% organic matter, 2% w/w Mg, 2%w/w Fe, 2% w/w Zn, 2% w/w Mn, 0.5% w/w Cu, 0.5% w/w B), compared to control and other variants.